2009
DOI: 10.1111/j.1439-0469.2009.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic relationships of species of Crenicichla (Teleostei: Cichlidae) from southern South America based on the mitochondrial cytochrome b gene

Abstract: Phylogenetic analysis using Bayesian inference, likelihood and parsimony methods was conducted on 60 complete mitochondrial cytochrome b sequences from 21 species of Crenicichla, including all species known from Uruguay (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
60
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(65 citation statements)
references
References 29 publications
0
60
0
5
Order By: Relevance
“…This supports an adaptive basis for a trade-off between those geophagine taxa feeding primarily from the substrate and those feeding above it. The Crenicichla clade encompasses 44 per cent of the species diversity of clade CAS and 35 per cent of the diversity of all geophagine cichlids, exhibits ecomorphological characteristics nearly unique among South American Neotropical cichlids and possesses as much body size and morphological disparity as many other Neotropical cichlid genera combined [18,20,21]. Evolution of the unique combination of feeding biomechanics probably permitted the evolution of a novel feeding strategy (fast-burst predators) among the Geophagini, allowing opportunities for rapid diversification of ecomorphological traits within this niche [51].…”
Section: (C) Adaptive Peaks and Key Innovationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This supports an adaptive basis for a trade-off between those geophagine taxa feeding primarily from the substrate and those feeding above it. The Crenicichla clade encompasses 44 per cent of the species diversity of clade CAS and 35 per cent of the diversity of all geophagine cichlids, exhibits ecomorphological characteristics nearly unique among South American Neotropical cichlids and possesses as much body size and morphological disparity as many other Neotropical cichlid genera combined [18,20,21]. Evolution of the unique combination of feeding biomechanics probably permitted the evolution of a novel feeding strategy (fast-burst predators) among the Geophagini, allowing opportunities for rapid diversification of ecomorphological traits within this niche [51].…”
Section: (C) Adaptive Peaks and Key Innovationsmentioning
confidence: 99%
“…org), and similar to clade GGD includes substrate-sifting benthivores in the genera Satanoperca and Acarichthys [20], as well as numerous (greater than 90) dwarf species, such as those within the genus Apistogramma, living in leaf litter habitats and probably picking benthic invertebrates from the substrate [19,20]. Clade CAS however, also includes Crenicichla (which includes within it the genus Teleocichla, see López-Fernández et al [17]; henceforth, the 'Crenicichla clade'), which comprises 90 described and numerous undescribed species of elongate-bodied predators feeding on fishes and invertebrates [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…These Uruguayan species are traditionally included in the C. missioneira and C. scottii species groups (Lucena & Kullander, 1992; extended by Kullander et al, 2010), and differ from the herein discussed taxa in a combination of color-pattern and meristic characters (Lucena & Kullander, 1992). The relationships of the new species with the Paraná River Crenicichla is also confirmed with analysis of molecular data (mitochondrial genes ND2 and cytochrome b) which included all at-present-known species from the Misiones province (Piálek et al, in prep.).…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic relationships within Crenicichla are still controversial. Based on a mitochondrial cytochrome b gene analysis, Kullander et al (2010) reported the monophyly of some previously defined Crenicichla species groups that were recognized based on morphology. Kullander (1990) presented a discussion on small species of Crenicichla from the Amazon basin.…”
Section: Introductionmentioning
confidence: 99%